2017
DOI: 10.1590/0037-8682-0163-2017
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the clinical distributions of Candida species and the emergence of azole-resistant non-Candida albicans species in public hospitals in the Midwest region of Brazil

Abstract: Introduction: Incidence and antifungal susceptibility of Candida spp. from two teaching public hospitals are described. Methods: The minimum inhibitory concentrations of fl uconazole, voriconazole, itraconazole, and amphotericin B were determined using Clinical Laboratory Standard Institute broth microdilution and genomic differentiation using PCR. Results: Of 221 Candida isolates, 50.2% were obtained from intensive care unit patients; 71.5% were recovered from urine and 9.1% from bloodstream samples. Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In the Midwest region of Brazil, it was confirmed the incidence of 35.3% of C. albicans and 64.7% NAC, besides to indicate the emergence of non-C. albicans species azole-resistant [48], while in Alagoas more than 3,000 isolates of Candida spp. have been observed in different clinical samples for 8 years; then, it is clear that yeasts of the genus Candida continue to be the most involved in superficial and systemic mycoses [30,47].…”
Section: Discussionmentioning
confidence: 73%
“…In the Midwest region of Brazil, it was confirmed the incidence of 35.3% of C. albicans and 64.7% NAC, besides to indicate the emergence of non-C. albicans species azole-resistant [48], while in Alagoas more than 3,000 isolates of Candida spp. have been observed in different clinical samples for 8 years; then, it is clear that yeasts of the genus Candida continue to be the most involved in superficial and systemic mycoses [30,47].…”
Section: Discussionmentioning
confidence: 73%
“…A study performed to Midwestern of Brazil also demonstrated an increase in the percentage of isolates resistant to azole: 57.6% of the Candida spp. samples showed decreased susceptibility (Mattos et al, 2017). A previous study suggested that long-term treatment with fluconazole might induce mutations that lead to drug resistance and, consequently, treatment failure (Peron et al, 2016).…”
Section: Susceptibility Assaymentioning
confidence: 92%
“…One of the most widely used antifungals in medical practice is fluconazole. However, Candida krusei is intrinsically resistant to this antifungal, and the resistance to this azole has also been reported in other Candida species [2,3]. More recently, the emergence of multidrug-resistant Candida auris in hospitals has caused panic worldwide [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In general, critically ill patients, such as those with an immature immune system or immune senescence, are at high risk of developing invasive Candida infection [2,3,5]. Five Candida species cause over 80 % of candidemia cases: C. albicans, C. glabrata, C. parapsilosis, C. tropicalis, and C. krusei [ 2,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation